Diagnostic potentiality of fractionated antigenof Aeromonas hydrophila isolated from gold fish,Carassius auratus (Linn.) - Maji, S; Mali, P; Joardar, S.N. (Indian Journal of Fisheries, 2011)
With the aim of isolating purified antigens of extra cellular products (ECP) ofA. hydrophila that might be exploited for early sero-diagnosis, bacteria wasisolated from ulcerative lesions of gold fish. Polypeptide profile of ECP of A.hydrophila showed 12 bands having molecular weight in the range of 22 – 55kDa in SDS-PAGE analysis. Fractionation (By DEAE-cellulose) and serologi-cal characterization of ECP were subsequently performed. One of thefractionated antigen (D1) possessing mainly of 45 kDa polypeptide revealedsero-reactivity with A. hydrophila antiserum having no cross-reactivecomponent(s) with related bacterial antigens, viz. Vibrio harveyi, V.alginolyticus and Pseudomonas fluorescence. Hence, 45 kDa polypeptide of ECPof A. hydrophila showing potentiality of sero-diagnosis should be given dueattention.